Metformin kinetics in healthy subjects and in patients with diabetes mellitus - Tucker, G. T. (1981)
1 The kinetics of metformin were studied after i.v. and oral administration in four healthy subjects and after oral administration in twelve maturity onset (Type II) diabetic patients. 2 After i.v. administration most of the dose was rapidly eliminated but with a mean `terminal' T(1/2) of 4 h measured up to 12 h in plasma and of 16 h measured up to 60 h from the urinary excretion rate. On average, 80% of the dose was recovered as unchanged drug in the urine with none detected in the faeces. 3 After single oral doses (0.5 and 1.5 g), maximum plasma concentrations and urinary excretion rates were observed at about 2 h with urinary recoveries of unchanged drug of 35-50% and faecal recoveries of about 30%. Urinary recoveries were significantly lower after the higher dose. Absolute oral bioavailability was 50-60% of the dose. 4 Deconvolution analysis showed that after a short lag-time, the available oral dose was absorbed at an exponential rate over about 6 h. Implications for the design of prolonged release dosage forms are discussed. 5 Plasma metformin concentrations measured throughout the seventh and fourteenth days of continuous 0.5 g twice daily treatment were accurately predicted from single dose data, although a discrepancy between observed and predicted trough levels reflected the existence of a slow elimination phase. Implications of the latter for a gradual accumulation of metformin in peripheral tissues and a possible association with lactic acidosis are discussed. 6 Renal clearance of metformin was highly correlated with creatinine clearance. However, a weaker relationship between total oral clearance of the drug and creatinine clearance suggests that the latter may not always be a reliable indicator of potential metformin accumulation owing to variability in absorption and possibly non-renal clearance of the drug,